The Madrasa Resistance Against Radicalism - Ahmad Salim (Nadwa: Jurnal Pendidikan Islam, 2019)
The background of this article is based on madrasa resistance to radicalism. The purpose of this study is to see how madrasa resistance to face radicalism. The type of this research is qualitative research and data collection methods with observation and in-depth interviews with selected respondents. This study uses Peter L Berger's theory of the fundamental dialectics of society-externalization, objectification, and internalization. The results showed that madrasa resistance to radicalism with social empowerment through the process of social construction (externalization, objectification, and internalization). The tolerant attitude of the community which is manifested in social humanitarian activities such as genduri, sambatan and kerja bakti is contracted by the madrasa as a subjective reality into objective reality, so that the anti-radicalism attitude in this society can become the norm for the madrasas to be deprived and implemented in the daily life of the madrasa. Abstrak Latar belakang artikel ini didasarkan pada resistensi madrasah terhadap radikalisme. Tujuan dari penelitian ini adalah untuk melihat bagaimana cara madrasah menghadapi radikalisme. Jenis penelitian ini adalah penelitian kualitatif dan metode pengumpulan data dengan observasi dan wawancara mendalam kepada responden terpilih. Penelitian ini menggunakan teori Peter L.Berger tentang dialektika fundamental masyarakat-eksternalisasi, objektifikasi dan internalisasi. Hasil penelitian menunjukkan bahwa madrasah menolak radikalisme dengan pemberdayaan sosial melalui proses konstruksi sosial (eksternalisasi, objektifikasi dan internalisasi). Sikap toleran dari masyarakat yang dimanifestasikan dalam kegiatan sosial kemanusiaan seperti genduri, sambatan dan kerja bakti dikontrak oleh madrasah sebagai realitas subjektif ke dalam realitas objektif, sehingga sikap anti-radikalisme dalam masyarakat ini dapat menjadi norma bagi madrasah untuk dicabut dan diimplementasikan di kehidupan sehari-hari madrasah.